Estradiol Treatment Ameliorates Acetic Acid-Induced Gastric and Colonie Injuries in Rats - (:unkn) unknown (My University, 2003)
To evaluate the role of estrogen treatment on the healing of acetic acid-induced gastric or colonic injury, rats were given 17β estradiol benzoate (0.001, 0.1, and 10 mg/kg) or vehicle for 7 days (following the induction of ulcer) or 4 days (following the induction of colitis) until they were decapitated. Food intake and fecal output were decreased by estradiol treatment but gastric emptying rate was not changed. Estradiol (10 mg/kg) reduced gastric ulcer index and colonic damage score compared to vehicle-treated groups. SEM and light microscopy demonstrated a significant reduction in the severity of ulcers and colitis by estradiol treatment. Gastric microscopic score was not changed by estradiol treatment, whereas in the colonic tissue score was significantly reduced. Elevated gastric MPO levels were reduced in gastric but not in colonic tissues as compared with corresponding vehicle groups. In conclusion, exogenous estradiol treatment at pharmacological doses improves the healing of both gastric and colonic injury induced by acetic acid in rats.
Keywords: Acetic acid; Estradiol; Experimental colitis; Myeloperoxidase; Ulcer index